Magnetic Quantum Dots Steer and Detach Microtubules From Kinesin‐Coated Surfaces. Issue 1 (9th October 2017) - Mahajan, Kalpesh D.; Cui, Yixiao; Dorcéna, C. Jenny; Bouxsien, Nathan F.; Bachand, George D.; Chalmers, Jeffrey J.; Winter, Jessica O.
Abstract : The microtubule (MT)‐kinesin system has been extensively studied because of its role in cellular processes, as well as its potential use for controllably transporting objects at the nanoscale. Thus, there is substantial interest in methods to evaluate MT properties, including bending radius and the binding energy of kinesin motor proteins to MT tracks. Current methods to identify these properties include optical tweezers, microfluidic devices, and magnetic fields. Here, the use of magnetic quantum dots (i.e., MagDots) is evaluated as a method to study MT‐kinesin interactions via applied magnetic forces. Magnetic fields are generated using a magnetic needle whose field gradient is quantified by finite element modeling (FEM). Magnetic force is applied to MagDot‐labeled MTs and demonstrated sufficient to steer and detach MTs from kinesin‐coated surfaces. Taking advantage of the dual‐functionality of MagDots, the magnetic force experienced by a single MagDot and the number of MagDots on MTs are determined. The total force exerted on MTs by MagDots is estimated to be ≈0.94–2.47 pN. This approach could potentially be used to interrogate MT properties and MT‐kinesin interactions, enhancing our biological understanding of this system and enabling further development of MT shuttles for nanotransport. Abstract : Microtubule‐kinesin interactions have generated great interest because of their potential application in nanotransport. Here, the authors presented a simple approach to manipulate microtubules and to measure microtubule‐kinesin unbinding forces using magnetic quantum dots and a magnetic needle. Using this approach, microtubules could be steered on and detached from t kinesin‐coated surfaces. This simple approach could potentially be applied to any process that utilizes microtubule shuttles.